China's foreign investment complaint mechanism: A new beginning of foreign investment governance reform? - Manjiao Chi; Zongyao Li (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
This Perspective discusses the development and features of China's foreign investment complaint mechanism (FICMs) and highlights China's first national FICM's potential roles as an alternative of investment dispute prevention and settlement, a measure of investment facilitation, and a factor in advancing China's foreign investment governance reform.
Keywords: 330